Church and settler in colonial Zimbabwe: a study in the history of the Anglican Diocese of Mashonaland/Southern Rhodesia, 1890-1925 - Welch, Pamela (Studies of religion in Africa 0083-5889, 2010)
Examines the history of the Anglican Diocese of Mashonaland/Southern Rhodesia in the period 1890-1925, when its institutions took shape and its religious character was formed. This book addresses questions of religion and empire, church and state and the complexities of relationship between the Church of England and her overseas extensions